Comparison of saponin composition and content in wild soybean (Glycine soja Sieb. and Zucc.) before and after germination. Issue 12 (2nd December 2014) - Krishnamurthy, Panneerselvam; Tsukamoto, Chigen; Takahashi, Yuya; Hongo, Yuji; Singh, Ram J; Lee, Jeong Dong; Chung, Gyuhwa
Abstract: Eight wild soybean accessions with different saponin phenotypes were used to examine saponin composition and relative saponin quantity in various tissues of mature seeds and two-week-old seedlings by LC–PDA/MS/MS. Saponin composition and content were varied according to tissues and accessions. The average total saponin concentration in 1 g mature dry seeds of wild soybean was 16.08 ± 3.13 μmol. In two-week-old seedlings, produced from 1 g mature seeds, it was 27.94 ± 6.52 μmol. Group A saponins were highly concentrated in seed hypocotyl (4.04 ± 0.71 μmol). High concentration of DDMP saponins (7.37 ± 5.22 μmol) and Sg-6 saponins (2.19 ± 0.59 μmol) was found in cotyledonary leaf. In seedlings, the amounts of group A and Sg-6 saponins reduced 2.3- and 1.3-folds, respectively, while DDMP + B + E saponins increased 2.5-fold than those of mature seeds. Our findings show that the group A and Sg-6 saponins in mature seeds were degraded and/or translocated by germination whereas DDMP saponins were newly synthesized. Graphical abstract: : Germination down-regulates group A saponins and up-regulates DDMP and group B saponins